Focus, Explore, Reflect and Apply (FERA) Learning Model: Developing Science Process Skills for Pre-Service Science Teachers - Budiman, Deni Moh; Gumilar, Surya; Rizal, Rahmat (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this study is to describe the application of Focus, Explore, Reflect, and Apply (FERA) learning model in improving science process skills for a pre-service science teacher in primary school. The stages of learning using the FERA learning model consist of four stages, namely focus, explore, reflect, and apply. The sample of this study was the students in the Primary School Teacher Education Study Program at STKIP Sebelas April Sumedang. This research was conducted using Quasy-Experimental method with Non-equivalent Control Group Design. The effectiveness of the treatment was obtained by giving the pretest and posttest to each class one time. The research data was processed by analyzing N-gain, normality test, and average difference using the Wilcoxon and Man Withney U tests. The results showed that the experimental class and the control class had significant mean differences between the science process skills data on pretest and posttest. This shows that learning using the FERA model is more effective in improving science process skills for pre-service primary school science teachers.